Coordinated river infrastructure decisions improve net social-ecological benefits. (1st October 2020) - Roy, Samuel G; Daigneault, Adam; Zydlewski, Joseph; Truhlar, Allison; Smith, Sean; Jain, Shaleen; Hart, David
Abstract: We explore the social, ecological, economic, and technical dimensions of sustainable river infrastructure development and the potential benefits of coordinating decisions such as dam removal and stream crossing improvement. Dam removal is common practice for restoring river habitat connectivity and ecosystem health. However, stream crossings such as culverts are often 15 times more abundant than dams and may pose similar ecological impacts. Using multi-objective optimization for a model system of 6100 dams and culverts in Maine, USA, we demonstrate substantial benefit-cost improvements provided by coordinating habitat connectivity decisions. Benefit-cost efficiency improves by two orders of magnitude when coordinating more decisions across wider areas, but this approach may cause inequitable resource distribution. Culvert upgrades improve roadway safety and habitat connectivity, creating cost-effective opportunities for coordinating and cost-sharing projects between conservationists and safety managers. Benefit-cost trends indicate significant overlaps in habitat and safety goals, encouraging flexible stakeholder collaborations and cost-sharing strategies.